Perlidungan Hukum Kemitraan Ojek Online Dengan Driver Pasca Diberlakukannya Undang-Undang Cipta Kerja - IB. Gede Agustya Mahaputra; I Made Aditya Mantara Putra; IA Cynthia Saisaria Mandasari (Fakultas Hukum, Universitas Warmadewa, 2023)
Public transport has an important role in economic development, because it is related to the distribution of goods and services. One of the most effective and efficient public transportation is the motorcycle taxi. Ojek is an informal public transportation in Indonesia in the form of motorbikes. In Indonesia, there is an online motorcycle taxi service that allows prospective passengers not to come to a base. Online motorbike taxis are another face of conventional motorbike taxis which are transformed using the touch of a smartphone-based technology application that is connected to the internet network. The problems raised in this study regarding legal protection arrangements are seen from the characteristics of agreements based on partnerships and the legal consequences that arise if the cooperation agreement is based on partnerships after the enactment of Law Number 11 of 2020 concerning Job Creation. The type of research used in writing this paper is a type of normative legal research with a problem approach used is a statutory approach and a conceptual approach. The results of the study show that the characteristics of the agreement generally consist of agreement, skills, the existence of a certain object, but in a partnership agreement these elements are also used but what distinguishes it is in a partnership agreement using the principles of mutual benefit, need and strengthening. The legal consequences of the work copyright law do not cover work relationships based on partnerships, which are only covered by working relationships based on work contracts (work agreements). If seen from the Law which is used as the legal basis, the principle of mutual benefit has not been fulfilled but it still benefits one of the parties so that it is still possible for breach of contract to occur.